Discontinuous and continuous space vector modulations for a nine-switch inverter - Jarutus N. (2017)
© 2016 IEEE. This paper proposes a developed space vector modulation (SVM) method of discontinuous and continuous modulation schemes for the nine-switch inverter. In this proposed, its simplicity is the mathematical analysis based on the two-level SVM principle in order to form the modulating waves. Later on, these modulating waves are compared with two carrier waves to generate the gating signals. As a consequence, the proposed SVM method provides a new switching state operation for the nine-switch inverter with the usefulness of more reduced switching commutation for both discontinuous and continuous modulation schemes compared with the conventional SVM method. Simulation results are given for validating the performance of the proposed method, demonstrating in good accordance with the theoretical analysis.